EFFORTS TO ERADICATE MOBILE PHONES IN CLASS II A LANGKAT NARCOTICS PRISON INSTITUTION AS AN EFFORTS TO PREVENT DISTURBANCES TO SECURITY AND ORDER IN PRISON - Amriza Putra; Abdul Razak Nasution; Mhd. Azhali Siregar (PT. Radja Intercontinental Publishing, 2024)
This study aims to determine: 1) What is the basis of the regulations governing the prohibition of mobile phone use in correctional institutions and how it is implemented. 2) What is the SOP for carrying out raids on mobile phone use in correctional institutions. 3) What are the legal sanctions given to prisoners who use mobile phones in correctional institutions. The research methodology used in this writing is an empirical legal method, namely an approach that examines secondary data first and then continues with conducting primary data research. The results of the discussion are as follows: 1) The basis of the regulations governing the prohibition of mobile phone use in correctional institutions is regulated in the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 8 of 2024 Article 24 paragraph (2) letter b and Article 26 letter i, as well as the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 6 of 2013 Article 4 letter j. The implementation of this prohibition involves strict supervision by correctional officers. 2) The SOP for carrying out raids on mobile phone use in correctional institutions is carried out by officers which begins with an assembly to provide direction for the implementation of the raid. Furthermore, a search of the blocks and residential rooms was carried out, officers removed one by one the prisoners/detainees who were in the targeted residential rooms while simultaneously conducting a body search. 3) The legal sanctions given to WBP who use cellphones in correctional institutions as regulated in Article 46 paragraph (3) letter f of the Indonesian Minister of Law and Human Rights Regulation Number 8 of 2024 are grouped into light sanctions in Article 45 paragraph (3), moderate sanctions in Article 45 paragraph (4), and heavy sanctions in Article 45 paragraph (4).